Third world women's literatures a dictionary and guide to materials in English - Fister, Barbara; Gale Group (Westport, Conn. Greenwood Press, 1995)
"Provides entries on works, writers, and themes found in Third World women's literatures in English and English translation. Presents a balance of well-known writers and emerging ones, contemporary as well as historical writers, and representative selections of genres, literary styles, and themes."--GVRL description.
Introduction -- The dictionary -- Appendix I: List of authors by region and country -- Appendix II: Chronological list of authors -- Appendix III: Resources for research -- Appendix IV: Anthologies -- Appendix V: Criticism -- Index.
Electronic reproduction.
Keywords: Women and literature -- Developing countries -- Dictionaries; Electronic books; Developing countries -- Literatures -- Dictionaries; Developing countries -- Literatures -- History and criticism -- Dictionaries; Developing countries -- Literatures -- Women authors -- Dictionaries